Comparison of the arch perimeter discrepancy in Javanese class I malocclusion: modified kesling vs. lundström analysis method at Dental Hospital Universitas Airlangga 2018-2024 - Winoto, Ervina Restiwulan; Alida, Alida; Dinda, Prasherly Anura (Majalah Kedokteran Gigi Indonesia, 2025)
Creating orthodontic treatment more efficiently in Indonesia requires the population's facial and jaw characteristics recognition as influenced by ethnic and gender characteristics. Myriad study model analysis methods are needed to evaluate a malocclusion’s treatment plan, such as modified kesling and lundström analysis which calculate Jaw Arch Perimeter (JAP) and Dental Arch Perimeter (DAP). Prior studies of different ethnicities and genders across global populations have demonstrated variations in results. Therefore, it is necessary to compare those two methods to ascertain the final result of arch perimeter discrepancy in Javanese class I malocclusion.  This study aims to prove the disparity in comparison of the arch perimeter discrepancy in Javanese class I malocclusion by modified kesling vs. lundström analysis method at Dental Hospital Universitas Airlangga 2018-2024. Applied inclusion criteria: Javanese ethnicity, age 18–25 years, permanent dentition (first molar to first molar), and no prior orthodontic treatment. It results in 53 samples. In lundström analysis, JAP is obtained by enumerating segmentally measuring pairs of teeth using a caliper. In the modified kesling, JAP is obtained by tracing the model on plastic mica. Then, continue by making pre-correction JAP with a marker and making post-correction JAP by measuring the ideal arch using a 0.1 mm copper wire. This study identifies a statistically significant final value difference between those two methods. This study identified statistically significant differences in arch perimeter values using modified kesling method and lundström analysis, whilst no significant differences in arch circumference by gender.